Preparation method of anti-aging natural rubber sealing ring

By introducing a composite antioxidant into the natural rubber sealing ring, a thermally reversible crosslinking system is constructed, which solves the problem of insufficient performance of traditional antioxidants during storage and use, and achieves a significant improvement in aging resistance at high temperatures.

CN120966103APending Publication Date: 2025-11-18HAINING JIACHENG RUBBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511178807.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Traditional antioxidants cannot simultaneously meet the anti-aging needs of natural rubber seals during storage and enhance their anti-aging performance during use, resulting in premature consumption of antioxidants and insufficient anti-aging effects during use.

Method used

A composite antioxidant is used, in which disulfide bonds are introduced into the main chain of the amine antioxidant molecule through graft polymerization, and imine bonds and borate ester bonds are grafted onto the side chain to construct a thermally reversible crosslinking system. The dispersibility and oleophobic and hydrophobic properties are improved by long-chain alkyl groups, forming a triple crosslinking network.

Benefits of technology

It significantly improves the aging resistance of the sealing ring, increases the initial thermal decomposition temperature to 222-228℃, and after 100 hours of continuous use at 150℃, the mass loss rate is less than 6%, and the tensile strength retention rate is over 76%, solving the problems of excessive consumption of antioxidants during storage and insufficient aging resistance during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120966103A_ABST
    Figure CN120966103A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an anti-aging natural rubber sealing ring, and relates to the technical field of rubber products. According to the invention, an amine anti-aging agent is used as a skeleton, disulfide bonds, imine bonds and boric acid ester bonds are orderly combined, and long-chain alkyl is introduced. The preparation method comprises the following steps: preparing the composite anti-aging agent, mixing in double temperature zones, and heating and vulcanizing in stages. The initial thermal decomposition temperature of the prepared sealing ring reaches 222-228 DEG C, and after the sealing ring is continuously used for 100 hours in a 150 DEG C temperature environment, the mass loss rate is less than 6%. And after being stored for 12 months at normal temperature, the tensile strength retention rate is over 94 percent. A disulfide bond is introduced to an amine anti-aging agent molecular chain to serve as a high-temperature response core group, an imine bond and a borate bond are grafted to a side chain, a triple cross-linked network is formed at high temperature, and the rubber cross-linking density is remarkably enhanced; meanwhile, long-chain alkyl improves the compatibility of the anti-aging agent and natural rubber and endows the surface with oleophobic and hydrophobic properties, medium erosion is reduced, and the aging resistance of the sealing ring in the use stage is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rubber product technology, specifically to a method for preparing an aging-resistant natural rubber sealing ring. Background Technology

[0002] In the field of industrial sealing, natural rubber (NR) seals are widely used due to their high elasticity, low compression set, and cost advantages. However, the unsaturated double bonds in the NR molecular chain give it inherent defects: insufficient heat resistance (long-term operating temperature ≤80℃, short-term heat resistance ≤120℃, and chain breakage easily at high temperatures); poor resistance to media (sensitive to oils and oxidizing media, and poor aging resistance).

[0003] Traditional antioxidants used in natural rubber sealing rings struggle to simultaneously address the aging prevention needs during storage and the enhancement of aging resistance during use. Existing technologies often employ single-function antioxidants, failing to address the multi-factor aging challenges. Furthermore, traditional antioxidants passively capture free radicals, unable to dynamically optimize performance based on changes in the sealing ring's operating conditions at different stages. This leads to premature consumption of antioxidants during storage and insufficient aging resistance during use, limiting the overall performance improvement and application scope expansion of natural rubber sealing rings.

[0004] Therefore, it is necessary to provide a method for preparing aging-resistant natural rubber sealing rings to solve the above-mentioned technical problems, thereby achieving differentiated anti-aging and aging-resistant performance improvement of natural rubber sealing rings during storage and use. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing an aging-resistant natural rubber sealing ring, so as to solve the problem that traditional antioxidants are difficult to simultaneously meet the anti-aging requirements during storage and the enhancement of aging resistance during use when applied to natural rubber sealing rings.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A method for preparing an aging-resistant natural rubber sealing ring includes the following steps:

[0008] 1. Preparation of composite antioxidant: By weight, mix 8-12 parts of an amine antioxidant, 10-14 parts of a reducing agent containing disulfide bonds, 6-10 parts of a crosslinking agent containing imine bonds, and 5-8 parts of a stabilizer containing borate ester bonds, and add the main reaction initiator to react and obtain an intermediate product. Among these, the amine antioxidant can be a common p-phenylenediamine antioxidant, such as N-phenyl-N'-isopropyl-p-phenylenediamine (4010NA); the reducing agent containing disulfide bonds can be dimethyl dithiopropionate; the crosslinking agent containing imine bonds can be N,N'-m-phenylenebismaleimide; and the stabilizer containing borate ester bonds can be trimethyl borate. The main reaction initiator is an azo initiator or a peroxide initiator, such as azobisisobutyronitrile (AIBN) or benzoyl peroxide (BPO), and the amount of the main reaction initiator is 0.5%-1.5% of the mass of the amine antioxidant.

[0009] A graft polymerization reaction is carried out by adding 4-8 parts of long-chain alkyl monomers and a grafting initiator to the intermediate product. The amount of grafting initiator added is 1-3% of the long-chain alkyl monomers. The reaction is carried out under nitrogen protection and at 50-70°C for 1-3 hours to complete the grafting, that is, to introduce long-chain alkyl groups (such as C12-C18) into the intermediate product, thus obtaining a composite antioxidant. The composite antioxidant is based on an amine antioxidant, with disulfide bonds introduced into its molecular backbone as high-temperature responsive core groups, and imine bonds and borate ester bonds grafted onto its side chains, respectively.

[0010] If the amount of amine antioxidant is less than 8 parts, its antioxidant function is insufficient; if it is more than 12 parts, it may initiate self-polymerization. If the amount of reducing agent containing disulfide bonds is less than 10 parts, the dynamic cross-linking network is incomplete; if it is more than 14 parts, the excess sulfur free radicals will lead to side reactions. If the amount of cross-linking agent containing imine bonds is less than 6 parts, the side chain cross-linking is insufficient; if it is more than 10 parts, it may become over-cross-linked and brittle. If the amount of stabilizer containing borate ester bonds is less than 5 parts, the thermal stability is insufficient; if it is more than 8 parts, the amount of easily hydrolyzed byproducts will increase. An excess (more than 1.5% of the mass of amine antioxidant) of the main reaction initiator will cause molecular chain breakage; an insufficient amount (less than 0.5% of the mass of amine antioxidant) will result in a low grafting rate.

[0011] If the amount of long-chain alkyl monomer is less than 4 parts, the hydrophobicity will be insufficient; if it is more than 8 parts, it may reduce the density of active sites in the antioxidant. An appropriate amount of grafting initiator can ensure a grafting rate of ≥85%, while an excessive amount will lead to impurities in the homopolymer; an insufficient amount will lead to a low grafting rate.

[0012] In the preparation of intermediate products, microfluidic synthesis technology was employed. The amine antioxidant raw material, the disulfide-bonded reducing agent, the imine-bonded crosslinking agent, and the borate ester-bonded stabilizer were each delivered to a micromixer via independent channels. The delivery flow rates were as follows: amine antioxidant raw material: 0.4-0.6 mL / min; disulfide-bonded reducing agent: 0.5-0.7 mL / min; imine-bonded crosslinking agent: 0.3-0.5 mL / min; borate ester-bonded stabilizer: 0.2-0.4 mL / min. The micromixer control parameters were as follows: temperature: maintained at 55-65℃ (below 55℃ would result in incomplete decomposition of the main reaction initiator; above 65℃ would cause excessive disulfide bond breakage, increasing side reactions); pressure: maintained at 1.2-1.8 MPa to ensure sufficient dissolution of the reactants by supercritical CO2; excessively low pressure would lead to uneven mixing. The reaction time should be 20-30 minutes. Too short a reaction time will result in insufficient grafting rate; too long a reaction time will lead to the accumulation of byproducts (such as sulfides). Maintaining a neutral pH within the micromixer can prevent imine hydrolysis caused by acid / base catalysis. Introducing an inert gas (N2) to maintain an anhydrous environment can prevent the hydrolysis of borate esters.

[0013] After obtaining the intermediate product, long-chain alkyl monomers are introduced into a micromixer at a flow rate of 0.3-0.4 mL / min. The micromixer control parameters are as follows: temperature controlled at 50-70℃ (excessive temperature will lead to degradation of the long-chain alkyl groups); reaction time of 1-3 hours (insufficient time will result in incomplete grafting); pressure reduced to 0.5-1.0 MPa to prevent long-chain alkyl chain breakage; pH maintained neutral within the micromixer; and inert gas (N2) introduced.

[0014] The synthesis of composite antioxidants involves free radical graft polymerization and molecular bridging reactions, with the core steps as follows:

[0015] (1) Free radical initiation stage

[0016] Initiator (BPO / AIBN) decomposition: Benzoyl peroxide (BPO) or azobisisobutyronitrile (AIBN) homolytically cleaves under heating conditions to generate free radicals (such as benzoyl free radicals or isobutyronitrile free radicals), which initiate the active site of amine antioxidants (such as 4010NA) (usually a benzene ring or NH bond adjacent to the amine group).

[0017] (2) Introduction of disulfide bonds in the main chain

[0018] Amine antioxidants react with reducing agents containing disulfide bonds: free radicals attack the SS bonds of the reducing agent, initiating sulfur free radicals, which then undergo electrophilic substitution with the benzene ring of the amine antioxidant, forming a disulfide bond-bridged structure in the main chain.

[0019] The reaction equation for the key reaction:

[0020]

[0021] Key control points: The breaking of disulfide bonds should be strictly controlled at 55-65℃ to avoid excessive cross-linking due to excessive temperature; the concentration of sulfur free radicals should be adjusted by the flow rate (0.5-0.7 mL / min) to avoid side reactions (such as excessive formation of thioethers).

[0022] (3) Grafting of side chain imine bonds and borate ester bonds

[0023] Imine bond formation: The maleimide group (C=C) of N,N'-m-phenylenebismaleimide undergoes a Michael addition reaction with the secondary amine group (-NH-) of the amine antioxidant to form a side-chain imine bond.

[0024] Reaction formula:

[0025] R-NH+maleimide→RN-CH(CO)-CH(CO)-

[0026] Key control points: Maintaining a neutral pH in the micromixer can prevent imine hydrolysis caused by acid / base catalysis; controlling the flow rate to 0.3-0.5 mL / min ensures reaction selectivity.

[0027] Boronate bond formation: The BO bond of trimethyl borate undergoes an ester exchange reaction with the hydroxyl (-OH) or amino (-NH) group in the antioxidant molecule to form a thermally reversible boronate bond.

[0028] Reaction formula:

[0029] B(OCH3)3+R-OH→ROB(OCH3)2+CH3OH

[0030] Key control points: Inert gas (N2) is introduced into the micro mixer to maintain an anhydrous environment, as trace amounts of water can cause the hydrolysis of borate esters; the flow rate is controlled at 0.2-0.4 mL / min to prevent excessively high local concentrations.

[0031] (4) Long-chain alkyl grafting

[0032] First, the grafting initiator decomposes. The key control is that the amount of grafting initiator should be 1-3% of the long-chain alkyl monomer; below 1% results in insufficient initiation, and above 3% leads to impurities in the homopolymer. Nitrogen protection (O2 < 50 ppm) prevents free radical quenching. Second, sulfur radicals or benzene ring radicals in the intermediate are initiated, activating the active sites of the intermediate. Then, the long-chain alkyl monomer is grafted onto the intermediate via free radical addition reactions, introducing long-chain alkyl groups; finally, chain termination is achieved through coupling or disproportionation.

[0033] After the reaction is complete, the product is extracted and purified using supercritical carbon dioxide. The temperature of the supercritical carbon dioxide is controlled at 35-45℃, close to the critical temperature of CO2 (31℃), to ensure solubility. The pressure is 5-8MPa to selectively dissolve unreacted monomers and small molecule byproducts. Under these conditions, the product is maintained for 60-90 minutes to allow impurities in the product to fully dissolve in the supercritical carbon dioxide. Then, the pressure is gradually reduced to 3-5MPa for decompression separation to separate the carbon dioxide containing impurities from the purified composite antioxidant. The purity is above 98%, and the purified composite antioxidant is collected.

[0034] 2. Mixing: Add 2-2.5 parts of compound antioxidant, 1-3 parts of vulcanizing agent, and appropriate filler to 100 parts of natural rubber raw rubber, and mix to obtain the compounded rubber. A dual-temperature zone mixing process is adopted during mixing, including the following steps:

[0035] First, the natural rubber raw material and the compound antioxidant are pre-plasticized in a low-temperature zone of 40-55℃ for 15-30 minutes. Under low-temperature conditions, the molecular chains of the natural rubber raw material can initially untangle, creating favorable conditions for the uniform dispersion of subsequent additives.

[0036] The raw materials are then transferred to a high-temperature zone of 60-70℃. A vulcanizing agent and filler are added in this zone. The vulcanizing agent is an organic peroxide vulcanizing agent or an amine vulcanizing agent, such as dicumyl peroxide (DCP) or triethylenetetramine. During mixing, ultrasonic-assisted dispersion technology is used. The frequency of the ultrasonic equipment is set to 20-30kHz, and the power is 150-200W. Ultrasonic-assisted dispersion technology is activated during the high-temperature mixing stage of the dual-temperature zone mixing process, with the ultrasonic action time being 5-10 minutes. The ultrasonic probe operates intermittently, with each operation lasting 1 minute and an interval of 30 seconds.

[0037] 3. Vulcanization: The above-mentioned rubber compound is vulcanized using a segmented heating vulcanization method. The first stage uses compression molding vulcanization, and the second stage uses hot air vulcanization to finally produce the sealing ring. The segmented heating vulcanization method specifically involves:

[0038] The first stage of compression molding and vulcanization involves increasing the temperature from 120℃ to 130℃ at a rate of 5℃ / min, maintaining a pressure of 10MPa, and vulcanizing for 6-10 minutes. The mold surface is coated with either polytetrafluoroethylene (PTFE) or boron nitride to prevent the rubber from sticking to the mold. During this stage, the rubber undergoes initial cross-linking, forming a certain cross-linked structure.

[0039] The second stage is hot air vulcanization: the temperature is gradually increased from 130℃ to 150℃ at a rate of 2℃ / min, and vulcanization lasts for 0.5-1 hours. The temperature gradient can precisely trigger the stepwise reaction of the thermally reversible crosslinking groups of the antioxidant, allowing the rubber to further crosslink and form a stable and dense crosslinked structure.

[0040] The antioxidant used in the preparation of the sealing ring of this invention is based on an amine antioxidant as the backbone, with long-chain alkyl groups introduced through graft polymerization. Furthermore, a composite thermally reversible crosslinking system is constructed, in which disulfide bonds, imine bonds, and borate ester bonds are orderly combined using molecular bridging technology. Disulfide bonds are introduced into the main chain of the amine antioxidant as a high-temperature responsive core group, while imine bonds and borate ester bonds are grafted onto the side chains. The long-chain alkyl groups significantly improve the dispersion uniformity of the antioxidant in the natural rubber matrix through nonpolar interactions, thereby enhancing apparent compatibility. Simultaneously, the long-chain alkyl groups form a low surface energy layer through dense -CH3 end arrangement, imparting oleophobic and hydrophobic properties (contact angle ≥105°) to the sealing ring, reducing the erosion of rubber by oil and moisture during use. The long-chain alkyl groups reduce media penetration through physical exclusion effects, while the thermally reversible crosslinking network repairs micro-damage through chemical bond recombination; both synergistically enhance durability. At room temperature, the three groups work synergistically to exert antioxidant and free radical scavenging effects. When the temperature rises to the operating temperature (120-180℃), the disulfide bonds homolytically cleave to generate sulfur free radicals, initiating initial crosslinking. The imine bonds undergo a reverse reaction to release active groups, and the borate ester bonds undergo transesterification, forming a triple crosslinking network that significantly enhances the crosslinking density of the rubber. The sealing ring prepared by this invention has an initial thermal decomposition temperature of 222-228℃ compared to sealing rings prepared using traditional antioxidants, and its mass loss rate is less than 6% after 100 hours of continuous use at 150℃.

[0041] More specifically, in this invention, the thermally reversible crosslinking groups of the composite antioxidant construct a triple crosslinking network at high temperatures, enhancing the crosslinking density of the rubber and improving the chemical stability of the material. When the sealing ring comes into contact with a chemical medium, the oleophobic and hydrophobic properties of the long-chain alkyl groups make it difficult for the medium to adhere to and penetrate into the rubber, reducing the direct contact between the chemical medium and the thermally reversible crosslinking network, lowering the risk of damage to the crosslinking network, thereby protecting the stable structure constructed by the thermally reversible crosslinking groups and maintaining the sealing performance of the sealing ring.

[0042] More specifically, the thermally reversible crosslinking network alters the physical structure of rubber, enhancing its mechanical properties. The presence of long-chain alkyl groups further optimizes these physical properties. On one hand, long-chain alkyl groups improve the compatibility of antioxidants with natural rubber, allowing the antioxidants to be more uniformly dispersed in the rubber matrix, ensuring a more uniform thermally reversible crosslinking reaction and avoiding localized performance differences caused by uneven antioxidant distribution. On the other hand, long-chain alkyl groups impart oleophobic and hydrophobic properties to the sealing ring surface, reducing volume expansion or mechanical property degradation caused by the adsorption of oils and moisture. Under high-temperature conditions, this property, in conjunction with the thermally reversible crosslinking network, prevents the rubber from softening and becoming sticky due to excessive absorption of media, maintaining the shape stability and sealing performance of the sealing ring, and ensuring good physical properties under various operating conditions.

[0043] More specifically, the thermally reversible crosslinking groups play an anti-aging role at different temperature stages, and the long-chain alkyl groups work in conjunction with them to enhance the overall durability of aging protection. During storage, the long-chain alkyl groups form a dense layer on the rubber surface through their non-polar ends (-CH3), physically blocking the penetration of polar media such as oxygen and moisture. This, together with the thermally reversible crosslinking groups that exert antioxidant and free radical scavenging effects at room temperature, protects the rubber. During use, when the temperature rises to 120-180℃, the triple crosslinking network is activated sequentially: disulfide bonds (120-150℃) dynamically exchange and repair micro-damage, imine bonds (150-170℃) release active groups to reorganize the network, and borate ester bonds (130-160℃) regulate the crosslinking density. The uniform dispersion of the long-chain alkyl groups ensures the efficient conduct of the thermally reversible reaction, significantly extending the service life of the sealing ring in hot oil media.

[0044] Compared with the prior art, the beneficial effects of the present invention are:

[0045] 1. This invention constructs a composite thermally reversible crosslinking system based on amine antioxidants, introducing disulfide bonds into the main molecular chain and grafting imine and borate ester bonds onto the side chains. At room temperature, these three chemical bonds synergistically exert antioxidant and free radical scavenging effects, effectively inhibiting rubber aging during storage. When the temperature rises to the operating temperature (120-180℃), the disulfide bonds homolytically cleave to generate sulfur free radicals, initiating initial crosslinking; the imine bonds undergo a reverse reaction to release active groups; and the borate ester bonds undergo transesterification, forming a triple crosslinking network. This significantly enhances the crosslinking density of the rubber and greatly improves its aging resistance during high-temperature use. Experimental data shows that after 100 hours of continuous use at 150℃, the mass loss rate is less than 6%; after aging at 120℃ for 500 hours, the tensile strength retention rate reaches over 76%, far superior to traditional natural rubber sealing rings.

[0046] 2. The long-chain alkyl groups introduced by the graft polymerization reaction in this invention improve the dispersibility of antioxidants in natural rubber, ensuring that the antioxidants can fully exert their effects. At the same time, the long-chain alkyl groups endow the sealing ring surface with oleophobic and hydrophobic properties, reducing the erosion of rubber by oily media and moisture, and enabling the resulting sealing ring to reach an initial thermal decomposition temperature of 222-228℃, which is an improvement compared to traditional natural rubber products.

[0047] 3. The composite antioxidant in this invention contains long-chain alkyl groups that form a good synergistic effect with the thermally reversible crosslinking groups. During storage, the -CH3 ends of the long-chain alkyl groups form a low surface energy layer on the rubber surface, blocking oxygen and moisture penetration. During use, when the temperature rises to 120-180℃, the triple crosslinking network is activated sequentially: disulfide bonds dynamically exchange to repair micro-damage, imine bonds release active groups to reorganize the network, and borate ester bonds regulate the crosslinking density. The uniform dispersion of the long-chain alkyl groups ensures efficient thermally reversible reactions, significantly extending the service life of the sealing ring in hot oil media. Attached Figure Description

[0048] Figure 1 Line graphs showing the comparative analysis of the mass loss rate of the sealing rings prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention after 100 hours of continuous use at 150°C. Detailed Implementation

[0049] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0050] Example 1: This example provides a method for preparing an aging-resistant natural rubber sealing ring, including the following steps:

[0051] 1. Preparation of composite antioxidant: Weigh 10g antioxidant 4010NA, 12g dimethyl dithiodipropionate, 8g N,N'-m-phenylenebismaleimide, and 6g trimethyl borate, and add 0.08g azobisisobutyronitrile (AIBN) initiator. Using microfluidic synthesis technology, each raw material was fed to a micromixer via independent channels for reaction. The flow rate of the amine antioxidant raw material was 0.5mL / min, the flow rate of the reducing agent containing disulfide bonds was 0.6mL / min, the flow rate of the crosslinking agent containing imine bonds was 0.4mL / min, and the flow rate of the stabilizer containing borate ester bonds was 0.3mL / min. The internal temperature of the micromixer was controlled at 60℃, the pressure was maintained at 1.5MPa, and the reaction time was 25 minutes to obtain an intermediate product. Eight parts of octadecyl vinyl ether and 0.1 parts of tert-butyl peroxide (TBPB) were added to the intermediate product, and the reaction was carried out at 60°C for 2 hours under nitrogen protection to complete the grafting, i.e., introducing long-chain alkyl (C18) groups through graft polymerization. A composite antioxidant was obtained. The product was purified by extraction using supercritical carbon dioxide. The supercritical carbon dioxide temperature was controlled at 40°C and the pressure at 7 MPa for 75 minutes. Then, the pressure was gradually reduced to 4 MPa for vacuum separation, and the composite antioxidant with a purity of 98.5% was collected.

[0052] 2. Mixing: Add 2.2g of the above-mentioned composite antioxidant to 100g of natural rubber raw rubber. First, pre-plasticize in a low temperature zone of 50℃ for 20min, then transfer to a high temperature zone of 65℃, and add 2g of dicumyl peroxide (DCP) vulcanizing agent and 35phr N330 carbon black filler (phr indicates the content of additives per 100 parts of resin). During the high temperature mixing stage, turn on the ultrasonic-assisted dispersion technology, set the ultrasonic frequency to 25kHz, the power to 180W, the ultrasonic action time to 7 minutes, and the ultrasonic probe works for 1 minute each time with a 30-second interval to obtain the compound rubber.

[0053] 3. Vulcanization: The compound rubber is vulcanized in stages with increasing temperature. The first stage is compression molding vulcanization, where the temperature is increased from 120℃ to 130℃ at a rate of 5℃ / min, the pressure is 10MPa, and the vulcanization time is 8 minutes. The mold surface is then coated with a polytetrafluoroethylene coating. The second stage is hot air vulcanization, where the temperature is gradually increased from 130℃ to 150℃ at a rate of 2℃ / min and the vulcanization time is 1 hour to obtain the sealing ring.

[0054] Example 2: This example provides a method for preparing an aging-resistant natural rubber sealing ring, including the following steps:

[0055] 1. Preparation of a composite antioxidant: Weigh 8g of antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer), 10g of dimethyl dithiodipropionate, 6g of N,N'-m-phenylenebismaleimide, and 5g of trimethyl borate, and add 0.08g of benzoyl peroxide (BPO) initiator. Microfluidic synthesis was employed, with the following flow rates for each raw material: amine antioxidant 0.4mL / min, reducing agent containing disulfide bonds 0.5mL / min, crosslinking agent containing imine bonds 0.3mL / min, and stabilizer containing borate ester bonds 0.2mL / min. The internal temperature of the micromixer was controlled at 55℃, the pressure maintained at 1.2MPa, and the reaction time was 30 minutes to obtain an intermediate product. Five parts of hexadecyl methacrylate and 0.1 parts of lauroyl peroxide were added to the intermediate product, and the reaction was carried out at 50°C for 3 hours under nitrogen protection to complete the grafting, i.e., the introduction of long-chain alkyl (C16) molecules through graft polymerization. The product was purified by supercritical carbon dioxide extraction at 35°C and 5 MPa for 90 minutes, followed by depressurization to 3 MPa for separation, yielding a composite antioxidant with a purity of 98.2%.

[0056] 2. Mixing: Add 2g of composite antioxidant to 100g of natural rubber raw rubber. First, pre-plasticize in a low-temperature zone at 40℃ for 30min, then transfer to a high-temperature zone at 70℃, and add 1.5g of triethylenetetramine vulcanizing agent and 30phr of silica filler. In the high-temperature zone, turn on ultrasonic-assisted dispersion at a frequency of 20kHz, a power of 150W, and an ultrasonic treatment time of 5 minutes. The ultrasonic probe operates in the same mode as in Example 1 to obtain the mixed rubber.

[0057] 3. Vulcanization: The compound rubber undergoes segmented temperature-increasing vulcanization. The first segment is compression molding vulcanization, where the temperature is increased from 120℃ to 130℃ at a rate of 5℃ / min, the pressure is 10MPa, and the vulcanization time is 6 minutes. The mold is then coated with a boron nitride coating. The second segment is hot air vulcanization, where the temperature is increased from 130℃ to 150℃ at a rate of 2℃ / min and the vulcanization time is 0.5 hours, resulting in the sealing ring.

[0058] Example 3: This example provides a method for preparing an aging-resistant natural rubber sealing ring, including the following steps:

[0059] 1. Preparation of composite antioxidant: Weigh 12g antioxidant 4010NA, 14g dimethyl dithiodipropionate, 10g N,N'-m-phenylenebismaleimide, and 8g trimethyl borate, and add 0.06g azobisisobutyronitrile (AIBN) initiator. During microfluidic synthesis, the flow rates of each raw material are as follows: amine antioxidant 0.6mL / min, reducing agent containing disulfide bonds 0.7mL / min, crosslinking agent containing imine bonds 0.5mL / min, and stabilizer containing borate ester bonds 0.4mL / min. The micromixer temperature is 65℃, the pressure is 1.8MPa, and the reaction time is 20 minutes to obtain an intermediate product. Add 4 parts dodecyl acrylate and 0.08 parts azobisisobutyronitrile (AIBN) to the intermediate product, and react at 70℃ for 1 hour under nitrogen protection to complete the grafting, i.e., introducing long-chain alkyl (C12) groups through graft polymerization. The compound antioxidant was purified by supercritical carbon dioxide extraction at 45°C and 8 MPa for 60 minutes, then separated by reducing the pressure to 5 MPa. The purity of the compound antioxidant was 98.8%.

[0060] 2. Mixing: Add 2.5g of composite antioxidant to 100g of natural rubber raw rubber. Pre-plasticize at a low temperature of 55℃ for 15min, then transfer to a high temperature of 60℃, and add 3g of dicumyl peroxide (DCP) vulcanizing agent and 20phr of talc filler. Disperse with ultrasound in the high temperature zone using a frequency of 30kHz, a power of 200W, and an ultrasound treatment time of 10min, keeping the ultrasound probe operating in the same mode to obtain the mixed rubber.

[0061] 3. Vulcanization: The compound rubber is vulcanized in stages with increasing temperature. The first stage is compression molding vulcanization, where the temperature is increased from 120℃ to 130℃ at a rate of 5℃ / min, the pressure is 10MPa, and the vulcanization time is 10min. The mold is then coated with a polytetrafluoroethylene coating. The second stage is hot air vulcanization, where the temperature is increased from 130℃ to 150℃ at a rate of 2℃ / min and the vulcanization time is 1h. This process produces the sealing ring.

[0062] Comparative Example 1: In this comparative example, the traditional single antioxidant 4010NA was used (without the addition of the composite antioxidant of this invention), and natural rubber sealing rings were prepared according to conventional mixing and vulcanization processes.

[0063] Comparative Example 2: In this comparative example, an antioxidant that does not introduce disulfide bonds was used. The preparation method of the natural rubber sealing ring includes the following steps:

[0064] Preparation process: Weigh 10g of antioxidant 4010NA, 8g of N,N'-m-phenylenebismaleimide (a crosslinking agent containing imine bonds), and 6g of trimethyl borate (a stabilizer containing borate ester bonds). Add 0.08g of azobisisobutyronitrile (AIBN) initiator and react in a micromixer under the same reaction conditions as in Example 1, but without the addition of a reducing agent containing disulfide bonds (dimethyl dithiopropionate). After obtaining the intermediate product, introduce long-chain alkyl groups (C18) through graft polymerization. Subsequent mixing and vulcanization steps are the same as in Example 1.

[0065] Comparative Example 3: In this comparative example, an antioxidant without imine bonds and borate ester bonds was used. The preparation method of the natural rubber sealing ring includes the following steps:

[0066] Preparation process: Weigh 10g of antioxidant 4010NA and 12g of dimethyl dithiodipropionate (a reducing agent containing disulfide bonds), add 0.08g of azobisisobutyronitrile (AIBN) initiator, and react in a micromixer under the same reaction conditions as in Example 1, but without the addition of a crosslinking agent containing imine bonds and a stabilizer containing borate ester bonds. After obtaining the intermediate product, a long-chain alkyl group (C18) is introduced through graft polymerization. Subsequent mixing and vulcanization steps are the same as in Example 1.

[0067] Comparative Example 4: No long-chain alkyl groups were introduced in this comparative example. The preparation method of the natural rubber sealing ring includes the following steps:

[0068] Preparation process: By weight, 10 parts of antioxidant 4010NA, 12 parts of a reducing agent containing disulfide bonds, 8 parts of a crosslinking agent containing imine bonds, and 6 parts of a stabilizer containing borate ester bonds were mixed and an initiator was added. The mixture was reacted in a micromixer to obtain an intermediate product, but no graft polymerization reaction was carried out to introduce long-chain alkyl groups (C18). Subsequent mixing and vulcanization steps were the same as in Example 1.

[0069] Comparative Example 5: In this comparative example, no graft polymerization reaction was used to introduce long-chain alkyl groups. The natural rubber sealing ring includes the following steps:

[0070] Preparation process: First, an intermediate product containing disulfide bonds, imine bonds, and borate ester bonds was prepared according to the method in Example 1. Then, octadecyl vinyl ether was directly physically mixed into the intermediate product, rather than introduced through graft polymerization. Subsequent mixing and vulcanization steps were the same as in Example 1.

[0071] The sealing rings prepared in the above embodiments and comparative examples were tested experimentally:

[0072] (1) Test the sample using the thermogravimetric analysis (TGA) method in ASTM E1131 and record the temperature corresponding to the starting point of mass loss, i.e. the initial thermal decomposition temperature.

[0073] (2) The sample was tested by the hot air aging test method in GB / T 3512, and the mass loss rate (%) was recorded after 100 hours of continuous use at 150℃.

[0074] (3) Test the sample using the rubber tensile properties test method in ASTM D412 to obtain the maximum stress at which the sample breaks, which is the tensile strength; after storing the sample at room temperature for 12 months, test it again and calculate and record the tensile strength retention rate (%).

[0075] (4) Test the sample using the rubber tensile properties test method in ASTM D412 to obtain the maximum stress at which the sample breaks, which is the tensile strength; test the sample again after aging at 120°C for 500 hours, and calculate and record the tensile strength retention rate (%).

[0076] The experimental data are compared in the table below and attached. Figure 1 As shown:

[0077]

[0078]

[0079] Note: Data is in mean format.

[0080] The experimental data shows that the embodiment demonstrates significant advantages over the comparative example in terms of thermal stability and aging resistance. Furthermore, it addresses the issues of premature consumption of antioxidants during storage and insufficient aging resistance during use.

[0081] Thermal stability: The initial thermal decomposition temperatures of Examples 1-3 reached 222-228℃, higher than the comparative examples. Comparative example 1 was only 205℃, comparative example 2 (without disulfide bonds) was 195℃, comparative example 3 (without imine and borate ester bonds) was 198℃, and comparative example 4 (without long-chain alkyl groups) was 202℃. This fully demonstrates that in the composite thermally reversible crosslinking system, disulfide bonds, imine bonds, and borate ester bonds work synergistically, and the effective combination of long-chain alkyl groups and antioxidants significantly enhances the thermal stability of the sealing ring, enabling it to withstand higher temperatures and be more stable in high-temperature environments.

[0082] Aging resistance: After 100 hours of continuous use at 150°C, the mass loss rate of the examples was less than 6%, while that of Comparative Example 1 was as high as 15%, Comparative Example 2 (without disulfide bonds) was 12%, and Comparative Example 3 (without imine and borate ester bonds) was 11%. After 12 months of storage at room temperature, the tensile strength retention rate of the examples was 94% or higher, while that of the comparative examples was lower, such as 73% for Comparative Example 1. After aging at 120°C for 500 hours, the tensile strength retention rate of the examples reached 76%-80%, while that of Comparative Example 1 was only 45%. This indicates that the composite thermally reversible crosslinking system effectively inhibits rubber aging during high-temperature use and long-term storage. The long-chain alkyl groups improve the compatibility of the antioxidant with natural rubber, reduce the erosion of the rubber by the medium, and jointly extend the service life of the sealing ring.

[0083] Solving the problem of premature consumption of antioxidants during storage: In traditional natural rubber sealing rings, antioxidants are consumed prematurely during storage, affecting their aging resistance in subsequent use. From the experimental data on the tensile strength retention rate after 12 months of storage at room temperature, Examples 1-3 achieved 95%, 94%, and 96% respectively, while Comparative Example 1, using a traditional single antioxidant, only achieved 73%. Comparative Examples 2-5 showed some improvement but still fell short of the examples; for instance, Comparative Example 2 (without disulfide bonds) achieved 85%. This indicates that the present invention, by constructing a composite thermally reversible crosslinking system, enables disulfide bonds, imine bonds, and borate ester bonds to synergistically exert antioxidant and free radical scavenging effects at room temperature, effectively slowing down the consumption rate of antioxidants and greatly improving the performance stability of the sealing ring during storage, successfully solving the problem of premature antioxidant consumption in traditional sealing rings during storage.

[0084] Addressing the issue of insufficient aging resistance during use: During use, traditional antioxidants fail to effectively improve the aging resistance of sealing rings under harsh conditions such as high temperatures and chemical corrosion. Experimental data shows that after 100 hours of continuous use at 150℃, the mass loss rate of Examples 1-3 was less than 6%, with an initial thermal decomposition temperature of 222-228℃; while Comparative Example 1 showed a mass loss rate as high as 15%, with an initial thermal decomposition temperature of only 205℃. After aging at 120℃ for 500 hours, the tensile strength retention rate of the Examples was 76-80%, while that of Comparative Example 1 was only 45%. Comparative Examples 2-5, due to not fully utilizing the key technologies of this invention, also exhibited significantly inferior performance compared to the Examples. This fully demonstrates that the present invention introduces disulfide bonds as the core groups for high-temperature response in the main molecular chain, and grafts imine bonds and borate ester bonds onto the side chains to form a triple crosslinking network at high temperatures, which significantly enhances the crosslinking density of the rubber. At the same time, the long-chain alkyl groups improve the compatibility of the antioxidant with natural rubber and endow the surface with oleophobic and hydrophobic properties, reduce media erosion, and greatly improve the aging resistance of the sealing ring during the service stage, effectively solving the problem of insufficient aging resistance of traditional sealing rings during the service stage.

[0085] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing an aging-resistant natural rubber sealing ring, characterized in that, Includes the following steps: (1) Preparation of composite antioxidant: By weight, 8-12 parts of amine antioxidant, 10-14 parts of reducing agent containing disulfide bond, 6-10 parts of crosslinking agent containing imine bond, and 5-8 parts of stabilizer containing borate ester bond are mixed and the main reaction initiator is added to obtain an intermediate product by reaction; then, long-chain alkyl groups are introduced into the intermediate product by graft polymerization to obtain composite antioxidant; (2) Mixing: Add 2-2.5 parts of the composite antioxidant prepared in step (1), 1-3 parts of the vulcanizing agent, and an appropriate amount of filler to 100 parts of natural rubber raw rubber, and mix to obtain the compound rubber; (3) Vulcanization: The above-mentioned compound rubber is vulcanized by a segmented heating vulcanization method, wherein the first segment is molding vulcanization and the second segment is hot air vulcanization, and finally a sealing ring is obtained.

2. The method for preparing the aging-resistant natural rubber sealing ring according to claim 1, characterized in that, In step (1), the amine antioxidant raw material, the reducing agent containing disulfide bonds, the crosslinking agent containing imine bonds, and the stabilizer containing borate ester bonds are respectively transported to the micro mixer for reaction through independent channels; The conveying flow rate of amine antioxidant raw materials is 0.4-0.6 mL / min, the conveying flow rate of reducing agents containing disulfide bonds is 0.5-0.7 mL / min, the conveying flow rate of crosslinking agents containing imine bonds is 0.3-0.5 mL / min, and the conveying flow rate of stabilizers containing borate ester bonds is 0.2-0.4 mL / min. The internal temperature of the micro mixer is controlled at 55-65℃, the pressure is maintained at 1.2-1.8MPa, and the reaction time is 20-30 minutes.

3. The method for preparing the aging-resistant natural rubber sealing ring according to claim 2, characterized in that, In step (1), the main reaction initiator is an azo initiator or a peroxide initiator, and the amount of the main reaction initiator is 0.5%-1.5% of the mass of the amine antioxidant.

4. The method for preparing the aging-resistant natural rubber sealing ring according to claim 1, characterized in that, In step (1), after obtaining the intermediate product, 4-8 parts of long-chain alkyl monomer and grafting initiator are added. The amount of grafting initiator added is 1-3% of the long-chain alkyl monomer. The reaction is carried out under nitrogen protection and at 50-70℃ for 1-3 hours to complete the grafting. The delivery flow rate of the long-chain alkyl monomer is 0.3-0.4 mL / min. The micro-mixer control parameters are: temperature controlled at 50-70℃, pressure reduced to 0.5-1.0 MPa, and reaction time of 1-3 hours.

5. The method for preparing the aging-resistant natural rubber sealing ring according to claim 4, characterized in that, In step (1), the grafting initiator is any one of lauroyl peroxide, tert-butyl peroxide, and azobisisobutyronitrile.

6. The method for preparing the aging-resistant natural rubber sealing ring according to claim 1, characterized in that, In step (1), after introducing long-chain alkyl groups, the product is extracted and purified using supercritical carbon dioxide. The temperature of the supercritical carbon dioxide is controlled at 35-45℃ and the pressure is 5-8MPa. Under these conditions, the product is maintained for 60-90 minutes to allow the impurities in the product to fully dissolve in the supercritical carbon dioxide. Then, by gradually reducing the pressure to 3-5 MPa, the carbon dioxide containing impurities was separated from the purified composite antioxidant, with a purity of over 98%, and the purified composite antioxidant was collected.

7. The method for preparing the aging-resistant natural rubber sealing ring according to claim 1, characterized in that, In step (2), a dual-temperature zone mixing process is adopted, including the following steps: a) First, pre-plasticize the natural rubber raw material and the composite antioxidant in a low temperature zone of 40-55℃ for 15-30 minutes. b) The material is then transferred to a high-temperature zone of 60-70°C, and a vulcanizing agent and filler are added. The vulcanizing agent is an organic peroxide vulcanizing agent or an amine vulcanizing agent.

8. The method for preparing the aging-resistant natural rubber sealing ring according to claim 7, characterized in that, During the mixing process, ultrasonic-assisted dispersion technology is used. The frequency of the ultrasonic equipment is set to 20-30kHz and the power is 150-200W. Ultrasonic-assisted dispersion technology is activated in the high-temperature mixing stage of the dual-temperature mixing process, and the ultrasonic action time is 5-10 minutes. The ultrasonic probe works intermittently, with each operation lasting 1 minute and an interval of 30 seconds.

9. The method for preparing the aging-resistant natural rubber sealing ring according to claim 1, characterized in that, In step (3), the segmented heating vulcanization method specifically refers to: First stage of molding vulcanization: The temperature is raised from 120℃ to 130℃ at a certain rate, the pressure is 10MPa, and vulcanization is carried out for a period of time. The mold surface is coated with polytetrafluoroethylene or boron nitride to prevent the rubber from sticking to the mold. The second stage is hot air vulcanization: the temperature is gradually increased from 130℃ to 150℃, and vulcanization is carried out for a period of time.

10. The method for preparing the aging-resistant natural rubber sealing ring according to claim 8, characterized in that, During the first stage of molding and vulcanization, the temperature rise rate is 5℃ / min, and the vulcanization time is 6-10min; During the second stage of hot air vulcanization, the temperature rise rate is 2℃ / min, and the vulcanization time is 0.5-1h.